Exome sequencing and directed clinical phenotyping diagnose cholesterol ester storage disease presenting as autosomal recessive hypercholesterolemia. - Stitziel, N; Fouchier, S; Sjouke, B; Peloso, G; Moscoso, A; Auer, P; Goel, A; Gigante, B; Barnes, T; Melander, O; Orho-Melander, M; Duga, S; et al. (2013)
OBJECTIVE: Autosomal recessive hypercholesterolemia is a rare inherited disorder, characterized by extremely high total and low-density lipoprotein cholesterol levels, that has been previously linked to mutations in LDLRAP1. We identified a family with autosomal recessive hypercholesterolemia not explained by mutations in LDLRAP1 or other genes known to cause monogenic hypercholesterolemia. The aim of this study was to identify the molecular pathogenesis of autosomal recessive hypercholesterolemia in this family. APPROACH AND RESULTS: We used exome sequencing to assess all protein-coding regions of the genome in 3 family members and identified a homozygous exon 8 splice junction mutation (c.894G>A, also known as E8SJM) in LIPA that segregated with the diagnosis of hypercholesterolemia. Because homozygosity for mutations in LIPA is known to cause cholesterol ester storage disease, we performed directed follow-up phenotyping by noninvasively measuring hepatic cholesterol content. We observed abnormal hepatic accumulation of cholesterol in the homozygote individuals, supporting the diagnosis of cholesterol ester storage disease. Given previous suggestions of cardiovascular disease risk in heterozygous LIPA mutation carriers, we genotyped E8SJM in >27 000 individuals and found no association with plasma lipid levels or risk of myocardial infarction, confirming a true recessive mode of inheritance. CONCLUSIONS: By integrating observations from Mendelian and population genetics along with directed clinical phenotyping, we diagnosed clinically unapparent cholesterol ester storage disease in the affected individuals from this kindred and addressed an outstanding question about risk of cardiovascular disease in LIPA E8SJM heterozygous carriers.